al-Khithob al-Nahwy fi al-Zahraween (Dirasah Nashshiyyah Tathbiqiyyah) - Salman, Shihab Ahmed (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2024)
This is a research paper that is presented as a commentary on the study of the researcher (Shahla Fattah Ahmed) that is entitled (The Grammatical Discourse in Al-Zahraween - an applied textual study) . There is no doubt that commenting and examining such a study deserves attention and importance. This is due to the fact that it deals with a miraculous text is still a subject of interpretation, analysis, and consideration of the contents of its contexts and its linguistic and expressive structures. Moreover its power to attract minds and stimulate souls to discover the secret of this miracle.